Assessment of the biological effect of Cu nanoparticles impregnated in polyethylene medical devices combined with the effect of LED radiation of the red and violet spectra on the ability of microorganisms to form biofilms and on daily biofilms - Mishyna, M. M.; Hopta, O. V.; Syrova, G. O.; Avramenko, V. L.; Mozgova, Y. R.; Malanchuk, S. G.; Makarov, V. O.; Dubovyk, O. S.; Marchenko, I. A.; Mishyn, Yu. M. (Journal of Education, Health and Sport, 2021)
For many years scientists around the world have been looking for an alternative to antibiotics due to rapidly growing level of resistance to them. LED light of various spectra and metal nanoparticles are considered as a promising alternative to antibiotics. In this work, we determined the complex effect of copper nanoparticles impregnated in high-pressure polyethylene and non-woven material with the effect of red and violet LED radiation on the ability of microorganisms to form biofilms and on already formed daily biofilms.